Urgent Splenectomy after Partial Splenic Embolization in Liver-Transplanted Patient: A Case Report - Jorge Herrador Benito; M. G. Zunzarren; T. Pozancos de Simón; L. Tortolero; R. Latorre Fragua; J. Nuño; E. Lobo (Case Reports in Transplantation)
We describe a 51-year-old-male. Three months after liver transplantation due to hepatitis C virus (HCV) hepatopathy, an HCV relapse was detected, and partial splenic embolization (PSE) was performed prior to antiviral treatment. Eleven days after PSE emergency splenectomy was performed due to the development of a splenic abscess, which is a rare but severe complication of PSE. Between May 2002 and March 2012, 18 PSEs have been performed in transplant patients in our centre. The patient presented here is the only case of splenic abscess and the only one who has needed surgery after complications of PSE.